(3eSGFd GdQO aj GdLOhds - (3Sdje GdaQVj GdehUdj, GHf GdMGaXs
(3ChdgG (B:s
(3CeG HYO , deG QCjJ ai TQM GdJQJjH dYHO Gddg GdbQVi GdTfThQi s
(3BNQgG (B:s
(3aJQSe GdLOhd GdSGOS hJLYgG ahbg bhSkG hJQbe ajg eG JUM efg GdeSFdI HYO edGMXI GdCUhd GdePchQI s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI Bd GdNWjH (B- (3GdehUd (B(171) s
Keywords: (3Yde GdaQGFVs